Impact of solidification on micromeritic properties and dissolution rate of self-nanoemulsifying delivery system loaded with docosahexaenoic acid. (2nd April 2020) - Ghosh, Dipanjoy; Singh, Sachin Kumar; Khursheed, Rubiya; Pandey, Narendra Kumar; Kumar, Bimlesh; Kumar, Rajan; Kumari, Yogita; Kaur, Gurmandeep; Clarisse, Ayinkamiye; Awasthi, Ankit; Gulati, Monica; Jain, Subheet Kumar; et al.
Abstract: Development of self-nanoemulsifying drug delivery systems (SNEDDS) of docosahexaenoic acid (DHA) is reported with the aim to achieve enhanced dissolution rate. The optimized composition of liquid SNEDDS (L-SNEDDS) formulation was Labrafil M1944 CS, 47% v/v Tween 80, 27% v/v Transcutol P, and 0.1% v/v DHA. L-SNEDDS were solidified using Syloid XDP 3150 as solid porous carrier. The droplet size, polydispersity index, zeta potential, percentage drug loading, and cloud point for L-SNEDDS were found to be 43.51 ± 1.36 nm, 0.186 ± 0.053, −19.20 ± 1.21 mV, 93.23 ± 1.71, and 88.60 ± 2.54 °C, respectively. Similarly, for solid SNEDDS (S-SNEDDS) the above parameters were found to be  57.32 ± 1.87 nm,  0.261 ± 0.043, −16.60 ± 2.18 mV, 91.23 ± 1.88, and 89.50 ± 1.18 °C, respectively. The formulations (L-SNEDDS, S-SNEDDS powder, and S-SNEDDS tablet) showed significant ( p <.05) improvement in dissolution rate of drug in 0.1 N HCl (pH 1.2) and phosphate buffer (pH 6.8) as compared to unprocessed DHA. In both the dissolution media, the dissolution rate was found more that 85% in 90 min. Absence of drug precipitation, phase separation, and turbidity during thermodynamic stability studies indicated that the developed SNEDDS were stable. Hence, it was concluded that SNEDDS have offered sufficient stability as well as dissolution rate of DHA.